Memórias do lixo: luta e resistência nas trajetórias de catadores e catadoras de materiais recicláveis da ASMARE - Romario Rocha Sousa (2018)
This paper aims to describe and problematize the context and conditions under which recyclers and waste pickers are inserted. As background, the experience of ASMARE, an association of collectors of recyclable material of the city of Belo Horizonte, is presented. The context of these subjects in the recycling chain is paradoxical. Although the legislation recognizes the profession of recyclable waste picker, the working conditions of these recyclers are still precarious. They usually work in unhealthy environments and are not guaranteed labor rights. In recent years, there has been a significant increase in cooperatives and gatherers associations, however, these collective ventures still face many economic and political difficulties. The approach of this dissertation is qualitative and the techniques that aided in the process of data collection were the oral history and the semistructured interviews. As a tool to analyze the corpus of this research, the Discourse Analysis was used. The main results show that the association, seen in other works as a pioneering experience in the country, is experiencing a crisis that is not only restricted to financial aspects, since its implications also resonate in the political formation of associates. Although they play an important role in society, recyclers and waste pickers face various adversities in their search for social recognition of their work and better working conditions. In this sense, the struggle story of the members of ASMARE represents the challenge of developing collective and social actions in a capitalist society, marked by inequality and exclusion